2008
DOI: 10.1152/physiolgenomics.00159.2007
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of ventricular myocyte electrophysiology

Abstract: The relative importance of regulatory versus structural evolution for the evolution of different biological systems is a subject of controversy. The primacy of regulatory evolution in the diversification of morphological traits has been promoted by many evolutionary developmental biologists. For physiological traits, however, the role of regulatory evolution has received less attention or has been considered to be relatively unimportant. To address this issue for electrophysiological systems, we examined the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 49 publications
2
68
0
Order By: Relevance
“…For example, the APD of the brown trout ventricular myocytes is 85 ms at +25°C and only 26 ms at +35°C , whereas in the similar-sized guinea pig, the APD of ventricular myocytes is 496 and 250 ms at +35°C and +25°C, respectively (Hume and Uehara, 1985), despite the higher f H in guinea pig (resting f H of 230-300 beats min −1 ) than brown trout (maximal f H =124 beats min −1 ) (Rouslin et al, 1995;Vornanen et al, 2014). Similarly, the ventricular APD 50 of the zebrafish, a species tolerating temperatures as high as +40°C (Cortemeglia and Beitinger, 2005), is only ∼60 ms at +36°C, which is much shorter than the ventricular AP of most laboratory mammals (200-300 ms at +34°C) with comparable f H values (Rosati et al, 2008;Vornanen and Hassinen, 2016).…”
Section: Thermal Adaptation Of Cardiac Excitabilitymentioning
confidence: 92%
See 1 more Smart Citation
“…For example, the APD of the brown trout ventricular myocytes is 85 ms at +25°C and only 26 ms at +35°C , whereas in the similar-sized guinea pig, the APD of ventricular myocytes is 496 and 250 ms at +35°C and +25°C, respectively (Hume and Uehara, 1985), despite the higher f H in guinea pig (resting f H of 230-300 beats min −1 ) than brown trout (maximal f H =124 beats min −1 ) (Rouslin et al, 1995;Vornanen et al, 2014). Similarly, the ventricular APD 50 of the zebrafish, a species tolerating temperatures as high as +40°C (Cortemeglia and Beitinger, 2005), is only ∼60 ms at +36°C, which is much shorter than the ventricular AP of most laboratory mammals (200-300 ms at +34°C) with comparable f H values (Rosati et al, 2008;Vornanen and Hassinen, 2016).…”
Section: Thermal Adaptation Of Cardiac Excitabilitymentioning
confidence: 92%
“…Indeed, in mammalian hearts, APD scales inversely with f H (and therefore with metabolic rate) -smaller animals have higher f H values and shorter APs (Rosati et al, 2008). An analogous relationship between f H and APD prevails in fish hearts under acute temperature changes; APD at the level of 50% repolarization (APD 50 ) shortens exponentially with increasing f H , giving a linear relationship when APD 50 is plotted against f H on a double log scale (Fig.…”
Section: Thermal Adaptation Of Cardiac Excitabilitymentioning
confidence: 99%
“…AP of the vertebrate heart is characterized by a long plateau phase, which is particularly prominent in ventricles and clearly shorter in the atrial chamber (Rosati et al 2008;Haverinen and Vornanen 2009). Similarly, atrial AP of L. fluviatilis was markedly shorter than ventricular AP (see "Electrocardiogram and HR").…”
Section: Cardiac Action Potentialsmentioning
confidence: 99%
“…Electrical excitation of a cardiac myocyte is the result of concerted activity of Na 1 , K 1 , and Ca 21 ion channels generating the AP (Rosati et al 2008). It is shown that lamprey ventricular myocytes express at least I Na , I Ca , I Kr , I K1 , and I K,ATP currents, which are also present in teleost cardiac myocytes (Paajanen and Vornanen 2001;Vornanen et al 2002a;Haverinen and Vornanen 2006;Hassinen et al 2008aHassinen et al , 2008bHassinen et al , 2011.…”
Section: Ion Current Basis Of Cardiac Excitationmentioning
confidence: 99%
“…cis-regulatory evolution | physiological scaling L arge differences in body mass among mammals require significant changes in heart rate and ventricular action potential duration to scale cardiac physiological function to body mass (1,2). These changes in cardiac function are produced by systematic changes in myocyte electrophysiological function and in the pattern and level of expression of multiple voltage-gated ion channels and transporters (2).…”
mentioning
confidence: 99%